Prevalence and associated behavioral symptoms of depression in mild cognitive impairment and dementia due to Alzheimer's disease. (17th December 2012) - Van der Mussele, Stefan; Bekelaar, Kim; Le Bastard, Nathalie; Vermeiren, Yannick; Saerens, Jos; Somers, Nore; Mariën, Peter; Goeman, Johan; De Deyn, Peter P.; Engelborghs, Sebastiaan
Abstract : Background: Mild cognitive impairment (MCI) is a clinical concept that categorizes subjects who are in an intermediate cognitive state between normal aging and dementia. The aims of this study are to determine the prevalence of significant depressive symptoms in MCI and Alzheimer's disease (AD) patients and to characterize the behavior associated with significant depressive symptoms in MCI and AD patients. Methods: A cross‐sectional analysis of baseline data from a prospective, longitudinal study on behavioral symptoms of dementia and MCI was performed. The study population consisted of 270 MCI and 402 AD patients. Behavioral assessment was performed by means of Middelheim Frontality Score, Behavioral Pathology in Alzheimer's Disease Rating Scale (Behave‐AD) and Cohen‐Mansfield Agitation Inventory. The presence of significant depressive symptoms was defined as a Cornell Scale for Depression in Dementia total score >7. Results: The prevalence of significant depressive symptoms in AD patients (25%) was higher compared with MCI patients (16%) ( p = 0.005). Patients with significant depressive symptoms showed an increased severity of frontal lobe symptoms, behavioral symptoms and agitation (Middelheim Frontality Score, Behave‐AD and Cohen‐Mansfield Agitation Inventory total scores; p < 0.001). Also, most of the individual frontal lobe and behavioral symptoms were more prevalent and severe, resulting in higher Behave‐AD global scores. Mild cognitive impairment patients with depressive symptoms showed more severe behavioral symptoms and more severe verbally agitated behavior than AD patients without depressive symptoms ( p < 0.001). Conclusions: Frontal lobe and behavioral symptoms are more prevalent and severe in MCI and AD patients with significant depressive symptoms as compared with patients without depressive symptoms. Copyright © 2012 John Wiley & Sons, Ltd.